A REVIEW STRATEGIES INTEGRATING MS ISO 31000:2010 RISK MANAGEMENT PROCESS INTO PROJECT LIFECYCLE FOR MALAYSIA LANDSCAPE PROJECT ORGANISATION - S.Muthuveeran, Adam Aruldewan; Mohd Tahir, Osman; Ibrahim, Roziya; Abd Karim, Saipol Bari; Rasidin, Elly Widiyanty (Journal of Surveying, Construction and Property, 2019)
Landscape projects in Malaysia have been facing prevailing issues with impact on project performance. These issues could be anticipated and addressed at an earlier stage by implementing effective risk management system. From previous studies on risk management system implementation into construction project as suggested by various studies show that there is no formal risk management system and integration of risk management process into a landscape project lifecycles. Considering this explorative potentiality within the gap, this study attempts to advance a conceptual framework by integrating the risk management process into a landscape project lifecycles. The conceptual framework is based on extensive reviews of related literatures in the variables but extensively covers two areas namely; MS ISO31000:2010 risk management process (RMP) and landscape project lifecycle (PLC) in developing the conceptual framework. A hypothetical framework for landscape project risk management process is then produced from the study and is surmise beneficial to enhance the understanding and application of risk management among landscape professionals for managing risk in Malaysia landscape development.